2014
DOI: 10.3945/jn.113.184838
|View full text |Cite
|
Sign up to set email alerts
|

Role of Walnuts in Maintaining Brain Health with Age

Abstract: Because of the combination of population growth and population aging, increases in the incidence of chronic neurodegenerative disorders have become a societal concern, both in terms of decreased quality of life and increased financial burden. Clinical manifestation of many of these disorders takes years, with the initiation of mild cognitive symptoms leading to behavioral problems, dementia and loss of motor functions, the need for assisted living, and eventual death. Lifestyle factors greatly affect the progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 58 publications
2
86
0
2
Order By: Relevance
“…In recent years, some researchers have found that Walnuts contain a number of potentially neuroprotective substances such as flavonoids and numerous polyphenolics which have both antiinflammatory and antioxidant properties and and it is shown that consumption of these compounds has a protective role against cisplatin-induced neurotoxicity without altering its anti-tumor activity [52,53]. An earlier study reported that Polyphenolic compounds found in walnuts not only reduce the oxidant and inflammatory load on brain cells but also improve interneuronal signaling, increase neurogenesis, and enhance sequestration of insoluble toxic protein aggregates [54]. In addition, Mohammad Shabani et al have found that walnut consumption might have a protective effect against neurotoxic injury in rat brain and it can maintain purkinje cells in normal morphology and attenuate neural changes in hippocampus [55,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some researchers have found that Walnuts contain a number of potentially neuroprotective substances such as flavonoids and numerous polyphenolics which have both antiinflammatory and antioxidant properties and and it is shown that consumption of these compounds has a protective role against cisplatin-induced neurotoxicity without altering its anti-tumor activity [52,53]. An earlier study reported that Polyphenolic compounds found in walnuts not only reduce the oxidant and inflammatory load on brain cells but also improve interneuronal signaling, increase neurogenesis, and enhance sequestration of insoluble toxic protein aggregates [54]. In addition, Mohammad Shabani et al have found that walnut consumption might have a protective effect against neurotoxic injury in rat brain and it can maintain purkinje cells in normal morphology and attenuate neural changes in hippocampus [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that rutin and caffeine as antioxidant substances have beneficial effects on memory function [23,24]. Walnut is rich in polyphenols and contains numerous ellagitannins [25,26], walnut polyphenol not only has antioxidant and anti-inflammatory activity but improves interneuronal signaling and increases neurogenesis [27,28]. In order to continue the previous research [17,29], this research work was designed to determine whether treatment with walnut polyphenol could restore the memory impairment in hypercholesterolemia mice.…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned in this review, polyphenolic compounds found in walnuts have both anti-inflammatory and anti-oxidant properties. Therefore, these compounds might reduce the oxidant and inflammatory load on brain cells, but in addition, they improve interneuronal signaling, increase neurogenesis, and enhance sequestration of insoluble toxic protein aggregates (Poulose et al, 2014). (Lin and Salem, 2007;Muthaiyah et al, 2011).…”
Section: Neurodegenerative Diseasementioning
confidence: 99%
“…Today, a combination of population growth, population aging, increase in cardiovascular diseases (CVDs), chronic diseases and disabling conditions, reduced quality of life (QOL), mortality, and increased financial burden has become a social concern (1). Primary prevention of these phenomena with a healthy diet containing nuts, such as walnuts (1), almonds (2), and pistachios (3), is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Primary prevention of these phenomena with a healthy diet containing nuts, such as walnuts (1), almonds (2), and pistachios (3), is possible. Research has shown that almonds have high unsaturated fats and affect the blood lipids (decrease triglycerides, total cholesterol, and LDL), and guarantees the health of women and men (4).…”
Section: Introductionmentioning
confidence: 99%